LINEARITY OF SERVICE QUALITY AND PUBLIC SATISFACTION IN GOVERNMENT HOSPITALS - Susanti, Andhini Indah; Ikawati, Fina; Husniati, Meylina; Aisah, Iis; Siswoyo, Mukarto; Khumayah, Siti (Ridwan Institute, 2024)
This study aims to analyze the relationship between service quality and community satisfaction in the outpatient installation of Kuningan Hospital. The research was carried out in May 2024 using a narrative descriptive method. Data collection was conducted using interviews, observations, and documentation. The results of the research show that there is a significant difference in perceptions related to the quality of health services. The quality of administrative services was considered very satisfactory by most of the informants. The tangible dimension of the installation was considered satisfactory. In the responsiveness dimension, it was found that officers showed a high level of professionalism and responsiveness in providing the needed help and information. The assurance dimension showed that informants appreciated accurate information and professionalism of officers. The findings of the study could inform strategies to enhance service delivery and meet the public's expectations more effectively.